Investigating the Role of Moral Leadership in Predicting of Job Behavior and Breaking the Organizational Silence - ali khaleghkhah; habibeh najafi; zahra shahi (Allameh Tabataba'i University Press, 2017)
The purpose of this study was investigating the role of moral leadership in predicting the development of job behavior and breaking the organizational silence. The research method chosen in this research is descriptive and survey method.The statistical population of the study consisted of employees of Islamic Azad university, Ardabil branch. Based on the Morgan table data,76 individuals were selected as statistical sample and collected from them by stratified random sampling. The data gathering tool in this research is of Organizational Clarity Questionnaire Van Dine etal(2003);Harry and Colleagues' Career Behavior(2004), and Moral Leadership at Carlson and colleagues (2011).to analyze the data, one-sample t-test, Pearson correlation coefficient and linear regression were used.the results of the research hypothesis test showed that the mean of ethical leadership and occupational behavior in the sample group was significantly higher than the average level(P<0.05)while the mean of organizational silence was moderate and There is no significant difference with the mean of the statistical population(P<0.05).Also,the research showed that there was a significant positive correlation between ethical leadership and job behavior (P<0.05)and organizational and organizational silence(P<0.05). Finally, the results of regression analysis showed that the components of ethical leadership dimensions of fairness, power sharing and transparency can significantly predict occupational behavior(P<0.05).among the components of ethical leadership, only subscription Power can predict organizational silence(P<0.05).the management of Islamic Azad university, Ardabil branch should pay attention to the style of leadership and the strengthening of its components in its organization to defeat the silence of human resources and positive job behavior.